One-step preparation of efficient SiO2/PVDF membrane by sol-gel strategy for oil/water separation under harsh environments. (8th November 2022) - Xu, Yuanlu; Yu, Yueling; Song, Chunyang; Zhu, Yi; Song, Chengwen; Fan, Xinfei; You, Zaijin
Abstract: The environmental pollution and resource loss caused by oil-water emulsion bring a severe threat to human's life. Superhydrophobic/superoleophilic membranes are considered as a wise choice for separating water-in-oil emulsions. However, the large-scale production of acid and alkali resistant, sustainable and efficient membranes remains an enormous challenge. In this study, a superhydrophobic/superoleophilic SiO2 /PVDF (SP) membrane was prepared through facile sol-gel strategy in one step. Hydrophobic SiO2 nanoparticles (NPs) were modified on PVDF membrane by hydrolysis and polycondensation reaction of tetraethyl orthosilicate (TEOS) and hexadecyltrimethoxysilane (HDTMS) as precursors. The low surface energy of the hydrophobic SiO2 NPs and the micro/nano rough structures similar to the waxy protuberances of lotus leaves constructed by nano-SiO2 played a crucial role in obtaining the superhydrophobic/superoleophilic property. The water contact angle (WCA) of the optimal SP membrane reached 152.4 ± 1.4°, while the oil droplets completely permeated the membrane in 1 s. Also, the fluxes of SP membrane for petroleum ether/water, n-hexane/water, and n-heptane/water were 3886 ± 140, 3551 ± 146 and 3763 ± 57 L m −2 h −1, respectively, and the separation efficiencies were stable above 99.7%. Moreover, the SP membrane showed excellent separation effects and stability under different chemical environments. Most significantly, it also displayed anti-fouling performance like lotus leaves. The results indicated that its separation efficiency still remained above 97% after 20 cycles. Therefore, these outstanding results ensured the possibility of large-scale production and practical application of the SP membrane. Graphical abstract: Image 1 Highlights: SiO2 /PVDF membrane was prepared by facile sol-gel strategy in one step. Displaying superhydrophobicity and superoleophilicity. High flux and separation effect for oil-water mixture. Demonstrating great acid and alkali resistance and anti-fouling performance.